The Relationship Between Green Supply Chain Integration and Sustainable Performance Among Manufacturing Firms in Malaysia - Low Kun Wai,; Hashim, Fazian (Research in Management of Technology and Business, 2025)
Green Supply Chain Management (GSCM) involves integrating environmental considerations into all stages of the supply chain process, including product design, material sourcing, production, and distribution to customers. In line with this, Green Supply Chain Integration (GSCI) has been introduced to align the environmental management practices of manufacturers, suppliers, and customers. Despite its importance, the adoption of GSCI practices remains limited, resulting in missed opportunities to optimize resource usage, reduce waste generation, and lower carbon emissions, all of which are critical for achieving sustainable performance objectives. This study aims to provide a deeper understanding of how green supply chain integration impacts sustainable performance. Specifically, the research focuses on examining the relationships between supplier integration, customer integration, internal integration, logistics integration, technology integration, and sustainable performance. The study targeted manufacturing companies in Johor Bahru that hold the Malaysian Standard (MS) ISO 14001 certification. A quantitative research approach is utilized, with data collected through a structured questionnaire distributed to management and operational staff in the manufacturing sector. Data analysis will be conducted using the Statistical Package for Social Sciences (SPSS). The anticipated findings of this research are expected to offer valuable insights for management, supporting them in achieving environmental objectives while maintaining high performance in response to demands from stakeholders, customers, and environmental regulations.